1996
DOI: 10.1111/j.1365-2648.1996.tb02681.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of nurses’ attitudes towards research: a factor analytic approach

Abstract: Despite considerable top-down pressure on nurses to undertake research, the available evidence suggests that relatively few nursing studies are submitted for publication. Given the need to increase the degree to which research informs practice, this shortfall in output must of necessity constitute a cause for concern. Therefore, it seems timely that a full-scale investigation into the possible reasons for non-submission is conducted. This study, therefore, in an attempt to meet this aim, used factor analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 9 publications
4
67
0
2
Order By: Relevance
“…Perceived congruence was reported between the role of researcher and male gender, and females presented in vignettes as good at research were viewed as likely to be poor nurses (Hicks, 1996b). Hicks (1996a) suggested that gender-role schemata and identity could have infl uenced people's perceptions of and attitudes towards the two job roles of researcher and practitioner.…”
Section: Research Gender Identity and Self-effi Cacymentioning
confidence: 97%
See 1 more Smart Citation
“…Perceived congruence was reported between the role of researcher and male gender, and females presented in vignettes as good at research were viewed as likely to be poor nurses (Hicks, 1996b). Hicks (1996a) suggested that gender-role schemata and identity could have infl uenced people's perceptions of and attitudes towards the two job roles of researcher and practitioner.…”
Section: Research Gender Identity and Self-effi Cacymentioning
confidence: 97%
“…Qualitative methods are suggested as congruent with 'relational and emotional skills stereotypically associated with women' and 'demand less abstraction from context and statistical analysis', skills stereotypically associated with males (Grant, Ward, & Rong, 1987, p. 856). A study of 856 published sociology papers (Grant et al, 1987) found that quantitative methods were most preferred by both males and females although use of qualitative methods was signifi cantly higher among females.A series of studies by Hicks (1995Hicks ( , 1996aHicks ( , 1996b in relation to nurses and midwives suggested that many traits ascribed to the researcher role were construed as masculine (e.g., ambition), while many traits associated with the clinician role were construed as feminine (e.g., sympathy). Perceived congruence was reported between the role of researcher and male gender, and females presented in vignettes as good at research were viewed as likely to be poor nurses (Hicks, 1996b).…”
mentioning
confidence: 98%
“…Reasons reported include being insecure with their chosen research methodology, lacking confidence to write, diminished confidence in their research, and insufficient time to pursue writing activities. 4,6 Editorials have been written that lament the fact that nurses do not publish research results as frequently as they should and implore nurses to consider publication as an obligation. 1,7 For those who choose to forge ahead and publish their research results, there are some obstacles that need to be navigated.…”
Section: Barriers To Researchmentioning
confidence: 96%
“…Em um estudo cujo objetivo consistia em analisar a atitude dos enfermeiros para com a pesquisa, os resultados evidenciaram cinco fatores considerados barreiras para a utilização de pesquisa, a saber: fator 1 -barreiras pessoais (subjetivas) dos enfermeiros; fator 2 -barreiras organizacionais (estruturais); fator 3 -reações dos médicos frente à pesquisa de enfermagem; fator 4 -reações de profissionais da saúde e fator 5 -impacto da pesquisa de enfermagem (18) . (18) .…”
Section: A Prática Baseada Em Evidênciasunclassified